Faktor Yang Mempengaruhi Status Gizi Remaja Usia 16-18 Tahun - Oktovina Indrasari; Ekawati Sutikno (Jurnal Kesehatan Indonesia, 2020)
Activities that are enhanced by the busy schedules of adolescents can be increased during their meals. Adolescent nutritional status needs to be considered for future health. Adolescent nutritional status can be used with energy consumption and physical activity. The aim is to determine the relationship of adolescent characteristics, energy consumption and physical activity with the nutritional status of adolescents aged 16-18 years. Observational research method with cross sectional research design. The population in this study were students of class X and class XI, while the sample used was 72 students. The sampling technique in this study was systematic random sampling. Data were collected by interview using a structured questionnaire for energy consumption and physical activity variables. The results of this study indicate that consumption with adolescent nutritional status has a relationship with a significant value of 0,000, p-value < 0.05. Physical activity with adolescent nutritional status has a significant value of 0.004, p-value < 0.05. The conclusions of this study indicate that there is a relationship between energy consumption and nutritional status and there is also a relationship between physical activity and nutritional status.